Effect of effective Ca/S ratio on sulfide morphology in a 303-ton heavy steel ingot with calcium treatment in molten steel - Qiuyue ZHOU; Ying REN; Juntao BA; Lifeng ZHANG (工程科学学报, 2024)
This paper investigated the effect of calcium treatment on the sulfide morphology of 303-ton 16Mn tube sheet ingots through industrial experiments. The defects in forgings without calcium treatment were mainly distributed axially near the top of the ingot and radially within half of the ingot center. The defects were mainly caused by large-size type II MnS inclusions. The three-dimensional distribution of MnS inclusions in the radial center of the ingot top was detected using a Micro-CT, and the MnS inclusions were mainly long strips and flake-shaped. The number density, average sphericity, and maximum diameter of the MnS inclusions were 0.77 mm−3, 0.53, and 1370 μm, respectively. In the industrial experiments, calcium treatment of molten steel was performed after vacuum-breaking during VD (Vacuum degassing) refining. Thermodynamic calculations were performed using FactSage 7.1 software. Calcium treatment modified the original solid Al2O3 inclusions into liquid calcium aluminate inclusions and reduced the precipitation temperature of MnS inclusions from 1244.7 ℃ to 1227.9 ℃. During the solidification and cooling process of the ingot, Ca preferentially combined with S to form CaS, which reduced the precipitation of MnS inclusions. Calcium modified the oxide inclusions in steel before modifying sulfides. Therefore, the effective calcium/sulfur ratio (Ca/Seff.) was proposed to characterize the effect of calcium treatment on the morphology of sulfides. Ca/Seff. is the atomic concentration ratio of effective calcium for modified sulfide to sulfur in steel. Ca/Seff. can be calculated by the total oxygen, sulfur, and calcium contents in steel. This formula is suitable for low sulfur steel with high cleanliness, and the mass fraction of sulfur in molten steel is >30×10−6. We analyzed the morphology of sulfide on the top of a Ca-treated heavy ingot. The effect of Ca/Seff. ratio on the morphology of the sulfide was studied by sampling every 1/4 from the radial center to the edge of the ingot. The aspect ratio of sulfide at the top of the ingot decreased gradually with increasing Ca/Seff. in steel. When Ca/Seff. in steel was 0.22, homogeneous MnS inclusions were observed in the sulfide, and the average aspect ratio was 1.59. After calcium treatment, the Ca/Seff. in the steel was greater than 0.8, and the average aspect ratio of sulfide at the top of the ingot was less than 1.2. CaS and MnS sulfide was precipitated with calcium aluminate inclusions as the core, and the precipitated sulfide was spherical with a significantly reduced size. Hence, calcium treatment effectively modified the sulfide in the ingot.